Ibm bagi Petambak Udang Tradisional di Desa Masaran, Kecamatan Banyuates, Kabupaten Sampang, yang Gulung Tikar Akibat Kasus Kematian Udang yang Terus Menerus [ Ibm For Traditional Shrimp Farmers In Masaran Village, Banyuates District, Sampang Region, That Capital Losted By Shrimp Dead Cases Continuoesly] - Sudarno Sudarno; Gunanti Mahasri; Kismiyati Kismiyati (Jurnal Ilmiah Perikanan dan Kelautan, 2014)
Abstract Tiger shrimp (Penaeus monodon Fab) is one of the economically important shrimp, until 1992 became the most important of non petroleum export commodity from fishery sector. Since the end of 1993 up to now, the Penaeus monodon Fab death level has been relatively high and due to this circumstance have been caused many ponds collapsed so that the shrimp production was dramatically declined for year by year. Banyuates District is one of the Sampang Region areas which have big fisheries potential, aspecially for the breakist water pond, that the topest as the other district. There are a lot of shrimp dead cases until now. But, so that 80% of breakist water pond were broken and not operational. The objective of this societies service activities is applicated a new shrimp culture technology with traditional plus Imuno-Biocirculation System. Imuno-Biocirculation System (SI-PBR) for increases the shrimp harvest at Candi District Region of Sidoarjo, at May until Desember 2013. The method using in the activity were socialitation/counseling, dempond and guiding to application of the SI-PBR model in one periode. Monitoring and evaluation about this result were done in one month after the activity ending. This result showed that a positive indication. There was the knowledges of the farmer in ceases by socialization, it also applicated a model in the right method for shrimp culture. There were also showed that the SI-PBR model can in ceased the shrimp harvest from 272,43 kg/ha to 854,66 kg/ha, it means was increased 313%. The conclution of this activity is the SI-PBR model can increased the shrimp harvest and can applicates in more larges area in Sidoarjo Region.